A behavioral intervention in a cohort of Japanese-Brazilians at high cardiometabolic risk - Bianca de Almeida-Pititto; Simon J Griffin; Stephen J Sharp; Amélia T Hirai; Suely G A Gimeno; Sandra R G Ferreira
OBJECTIVE: To assess the effect of a health promotion program on cardiometabolic risk profile in Japanese-Brazilians. METHODS: A total of 466 subjects from a study on diabetes prevalence conducted in the city of Bauru, southeastern Brazil, in 2000 completed a 1-year intervention program (2005-2006) based on healthy diet counseling and physical activity. Changes in blood pressure and metabolic parameters in the 2005-2006 period were compared with annual changes in these same variables in the 2000-2005 period. RESULTS: During the intervention, there were greater annual reductions in mean (SD) waist circumference [-0.5(3.8) vs. 1.2(1.2) cm per year, p<0.001], systolic blood pressure [-4.6(17.9) vs. 1.8(4.3) mmHg per year, p<0.001], 2-hour plasma glucose [-1.2(2.1) vs. -0.2(0.6) mmol/L per year, p<0.001], LDL-cholesterol [-0.3(0.9) vs. -0.1(0.2) mmol/L per year, p<0.001] and Framingham coronary heart disease risk score [-0.25(3.03) vs. 0.11(0.66) per year, p=0.02] but not in triglycerides [0.2(1.6) vs. 0.1(0.42) mmol/L per year, p<0.001], and fasting insulin level [1.2(5.8) vs. -0.7(2.2) IU/mL per year, p<0.001] compared with the pre-intervention period. Significant reductions in the prevalence of impaired fasting glucose/impaired glucose tolerance and diabetes were seen during the intervention (from 58.4% to 35.4%, p<0.001; and from 30.1% to 21.7%, p= 0.004, respectively). CONCLUSIONS: A one-year community-based health promotion program brings cardiometabolic benefits in a high-risk population of Japanese-Brazilians.